Ta’ṡīri al ‘Ughniati al ‘Arabiyyati li Tasyjī’i Ta’allumi al Lughati al ‘Arabiyyati ‘inda al Talāmīżi fī Rauḍati al Aṭfāli “Almīrā” fī Aur Duri Madīnati Jāmbi - Ferty, Feila Deo; Sudiarti, Sri (Al-Uslub: Journal of Arabic Linguistic and Literature, 2020)
The purpose of this study is to: 1) look at the influence of Arabic songs on the spirit of learning Arabic as well as improve the ability of Arabic children with song method 2) to know the change in attitude that occurs towards Arabic language songs with Arabic language songs 3) students can react well to the meaning of Arabic language songs given. This research is very useful in analyzing solid types of literature for psychological problems. Songs and music have a strong relationship with psychological circumstances. The type of research used is qualitative research. Can be inferred from the results of this study :1) Arabic songs can increase the spirit of learning Arabic in children 2) students are motivated and more spirit Arabic language with song methods as well as songs give knowledge about behavior.